Fundamentals of carrier transport - Lundstrom, Mark (Cambridge : Cambridge University Press, 2000)
Fundamentals of Carrier Transport is an accessible introduction to the behaviour of charged carriers in semiconductors and semiconductor devices. It is written specifically for engineers and students without an extensive background in quantum mechanics and solid-state physics. This second edition contains many new and updated sections, including a completely new chapter on transport in ultrasmall devices. The author begins by covering a range of essential physical principles. He then goes on to cover both low- and high-field transport, scattering, transport in devices, and transport in mesoscopic systems. The use of Monte Carlo simulation methods is explained in detail. Many homework exercises are provided and there are a variety of worked examples. The book will be of great interest to graduate students of electrical engineering and applied physics. It will also be invaluable to practising engineers working on semiconductor device research and development.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Includes bibliographical references and index.
MNS
HYE Trade International
Keywords: Semiconductors; Electron transport